Some Information about Austria and Egyptian Dialects - Jordania, Alex (Actual Problems of Kartvelology, 2013)
The article refers to the Austrian and Egyptian dialects. The main characteristics of the Austrian (Viennese) dialect are: shortening of words in literary language, deformation of diphthongs, special ‘Austriisms’. Unique case emerged from Cairo dialect, q is not replaced by hamza neither specific ‘Egyptisms’. Austrian society and the government tries to develop their literary language. There is the society which is studying a classic writer - Fr. Grillparzer in Austria. The language of universities across the whole Austria is the state language – German. The government and the population of Egypt pay great attention to the literary language. Literary level of the published books are high.